Reflections on emigration aspirations from young, educated people in small Balkan countries: A qualitative analysis of reasons to leave or stay in North Macedonia - Parker, K. A.; Hester, E. B.; Geegan, S. A.; Ciunova-shuleska, Anita; Palamidovska-sterjadovska, Nikolina; Ivanov, B. (My University, 2022)
For small, low-to-middle-income countries such as North Macedonia, the prospect of young, educated people leaving their place of residence (i.e. emigrating) can have significant negative societal-level effects. Understanding the complexity of the brain-drain phenomenon and its antecedents is critical to developing multi-level (i.e. global, societal, and individual) strategic solutions. A qualitative analysis of several focus-group interviews was used to understand young, educated residents’ reasons either for emigrating or for remaining in North Macedonia. Two overarching themes served to organise the participant-identified drivers for emigration and those opposed to it. Three sub-themes emerged describing the factors for emigration: 1) a lack of professional opportunities, 2) institutional systems, and 3) cultural tightness. Likewise, three sub-themes emerged describing the factors for staying: 1) community, 2) culture and 3) social responsibility. Insights serve to contextualise some of the experiences of young, educated people in small, low-to-middle-income, countries which impact on their emigration decisions.
Keywords: North Macedonia, Balkans, migration aspirations, emigration-decision conflict, brain drain